E-Government initiatives in Palestine - Elgharabawy, Mohamed; Ayu, Media Anugerah (IIUM Press, 2011)

(untitled)
Even up until today, Palestinian govemment still has to deal with many challenges and tests in ensuring the management of Palestine can be done efficiently. But despite the condition, efforts are flowing in order to give Palestinian the best services and to meet their requirements from time to time. One of the visible works is the initiative to established E-Govemment, which has started since 2005 and is ongoing until today. This chapter aims to give reader brief overviews and recommendations regarding some of these initiatives by Palestinian Govemment as well as the IT policies and IT infrastructures in Palestine.